An analysis on taxation of South African residents who are employed and working outside the territorial borders of South Africa - Salie, Mogamat Shakir (Department of Commercial Law, 2023)
I am an Operational Specialist in the learning and development department at my company and I am often faced with questions on the tax treatment of employed individuals working abroad. It is for this reason that I have chosen to dedicate my research in this area. South African tax legislation on the exemption of foreign employment income has been amended with effect from 1 March 2020. These amendments affect the taxation of South African tax residents who are employed and working outside the territorial waters of South Africa. Furthermore, these amendments do not consider the exemption of non-employment foreign income. This analysis has only considered employed individuals who are tax resident in South Africa and who have not formally emigrated from South Africa. The aim of this analysis is focused on the equitable and neutral tax treatment between employment income and income earned from other services rendered following the amendments. I have centred my analysis around equity and neutrality by comparing the different tax treatment of employment income and other forms of income. This analysis seeks to answer whether the amendments to the tax legislation support equity and neutrality. The key findings from this analysis have given me a better understanding of the rules and regulations around the amendments. I am now able to offer sound advice to my clients who in turn will make more informed decisions when planning their international employment assignments. In addition to the above, I hope that my analysis below will contribute towards any future research that may be done in this area.